Determinant values in the medical act of prescribing in the Portuguese context - Pinto, J.; Ferreira da Silva, A.; Curto, J. (Journal of Medical Marketing, 2010)
he purpose of this work is to identify and understand the preferential hierarchy of values set by the medical profession in the act of prescribing. Our target population consisted of physicians with practice in Portugal. From this universe, a random sample of 102 doctors was selected as the basis for this investigation. To achieve our aim, we used conjoint analysis as the principal statistical tool. Briefly, the main results can be described as follows: statistically significant results demonstrated that great care is taken by physicians to use pharmaceutical products with demonstrably greater effectiveness. Nevertheless, it was also observed that institutional brands play an important role in choosing the product prescribed.